Vertical distribution of heavy metals in soil profile of peri-urban areas of Haryana - SAVANOOR, VINAYAK V; YADAV, RAJPAUL; LOUHAR, GANPAT (The Indian Journal of Agricultural Sciences, 2021)
Soil serves as a sink for various heavy metals where they present long period of time in the soil and create a manyharmful effects on soil health. A survey was carried out in peri-urban areas of Mohindergarh and Narnaul city, Haryanairrigated by sewage and tube-well water. Study was conducted on vertical distribution of heavy metals in profile soilsamples. Soil samples were analyzed for initial properties of soil and DTPA extractable heavy metals (Zn, Cu, Cd,Cr, Pb, Ni and Co). The results revealed that the soluble heavy metals, viz. Zn, Cu, Cr, Cd, Pb and Co content in bothsewage and tube-well irrigated profile soil samples decreased with increased depth of soil in both Mohindergarh andNarnaul areas. But, the Ni content increased with depth in both areas of sewage and tube-well irrigated soils. It isconcluded that the profile soil samples were found below the permissible limit of soluble heavy metals concentration.